Do patients with "pure" chronic fatigue syndrome (neurasthenia) have abnormal sleep? - Sharpley, A; Clements, A; Hawton, K; Sharpe, M (1997)
OBJECTIVE: To determine whether patients with "pure" chronic fatigue syndrome (neurasthenia) have sleep abnormalities which may contribute to subjective measures of daytime fatigue. METHOD: Sleep characteristics of 20 patients meeting research criteria for chronic fatigue syndrome (CFS) but not depression, anxiety, or sleep disorder were compared with sleep characteristics of 20 healthy subjects matched for age and sex. Measures of sleep included a) subjective interview reports and sleep diaries and b) home-based polysomnography. RESULTS: Patients with CFS complained of poor quality unrefreshing sleep. They also napped during the day. Polysomnograph data showed no difference in actual nocturnal sleep time between the two groups although patients with CFS spent significantly longer in bed (p < .01), slept less efficiently (p < .03), and spent longer awake after sleep onset (p < .05). The polysomnographs of seven patients with CFS and one healthy subject were regarded as significantly abnormal. Five patients and one healthy subject had difficulty maintaining sleep. One patient had a disorder of both initiating and maintaining sleep and one patient woke early. CONCLUSIONS: Patients with "pure" CFS complain of unrefreshing sleep but only a minority have a clearly abnormal polysomnograph. The most common abnormality is of long periods spent awake after initial sleep onset. Although sleep abnormalities may play a role in the etiology of CFS, they seem to be unlikely to be an important cause of daytime fatigue in the majority of patients. However, pharmacological and behavioral methods that improve sleep quality may be an important component of a pragmatically based treatment package for patients who do have abnormal sleep.